The Voyage of A Heroic Pirate : Hero's Journey in Eiichiro Oda's One Piece - Bagaskara Wijayakusuma Putera Dwipa (LITERA KULTURA : Journal of Literary and Cultural Studies, 2022)
The journey of a hero is a theory that was developed by Joseph Campbell. This theory is made to explain the development of a main character while doing some adventures. There are seventeen steps to describe how can the main character wanders from one side to another to get that he wants. In this article, the writer wants to analyze the story of one of the famous manga, One Piece that is written by Eiichiro Oda based on the theory of Hero's Journey. The writer explains the journey of the main character of One Piece, named Monkey D. Luffy in the first saga of One Piece by using the seventeen steps that was developed by Campbell.